2018
DOI: 10.1021/acs.biomac.8b01093
|View full text |Cite
|
Sign up to set email alerts
|

Design of Modular Polyhydroxyalkanoate Scaffolds for Protein Immobilization by Directed Ligation

Abstract: In vivo-assembled polyhydroxyalkanoate (PHA) particles have been successfully bioengineered to display foreign protein functions toward high-value applications in medicine and industry. To further expand the design space of PHA particles toward immobilization of various functional proteins, we developed a tunable modular protein immobilization method implementing the SpyCatcher/SpyTag chemistry. We successfully displayed the SpyCatcher protein using translational fusion with the Ralstonia eutropha PHA synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 88 publications
5
52
0
Order By: Relevance
“…However, underlying molecular mechanisms of PHA particle formation still remain unknown, which intrinsically limits control of their physicochemical properties. For example, a few studies reported that fusing different proteins to PhaC influences the PHA production yield over biomass, particle size distribution, surface charges, and purity of the target protein (Rubio-Reyes et al, 2016;Gonzalez-Miro et al, 2018a,b;Wong and Rehm, 2018). Decorating PHA particles with proteins using PhaC synthase as an anchoring domain can also cause varying distribution and density of respective proteins on the PHA particles (Hay et al, 2015;Wong and Rehm, 2018).…”
Section: Magnetosome Membrane Protein Mms13mentioning
confidence: 99%
See 3 more Smart Citations
“…However, underlying molecular mechanisms of PHA particle formation still remain unknown, which intrinsically limits control of their physicochemical properties. For example, a few studies reported that fusing different proteins to PhaC influences the PHA production yield over biomass, particle size distribution, surface charges, and purity of the target protein (Rubio-Reyes et al, 2016;Gonzalez-Miro et al, 2018a,b;Wong and Rehm, 2018). Decorating PHA particles with proteins using PhaC synthase as an anchoring domain can also cause varying distribution and density of respective proteins on the PHA particles (Hay et al, 2015;Wong and Rehm, 2018).…”
Section: Magnetosome Membrane Protein Mms13mentioning
confidence: 99%
“…For example, a few studies reported that fusing different proteins to PhaC influences the PHA production yield over biomass, particle size distribution, surface charges, and purity of the target protein (Rubio-Reyes et al, 2016;Gonzalez-Miro et al, 2018a,b;Wong and Rehm, 2018). Decorating PHA particles with proteins using PhaC synthase as an anchoring domain can also cause varying distribution and density of respective proteins on the PHA particles (Hay et al, 2015;Wong and Rehm, 2018). Hooks et al (2013) also pointed out that displaying N-acetylneuraminic acid aldolase (NanA) from E. coli on PHA particles through N-and C-terminal fusion of PhaC resulted in varying catalytic performance .…”
Section: Magnetosome Membrane Protein Mms13mentioning
confidence: 99%
See 2 more Smart Citations
“…From a biotechnological perspective, these proteins have a high a nity toward the polymeric surface, and they can be usefully employed for immobilization of target proteins by engineering genetic fusions. Indeed, a number of groups have demonstrated successful immobilization of proteins onto PHA supports [11][12][13][14][15] through fusion with PHA-binding proteins, including phasins.…”
Section: Introductionmentioning
confidence: 99%